Anti-establishment versus authoritarian populists and support for the strong(wo)man - Anna Brigevich; Andrea Wagner (Frontiers in Political Science, 2025)
This paper contributes to the growing demand-side literature on populism by investigating how different types of populist attitudes shape support for strongman leaders. By capitalizing on popular discontent with the political establishment, populist leaders often ascend to power through democratic means, only to consolidate authority and weaken the very institutions that facilitated their rise. We argue that a major obstacle to understanding populist support lies in the tendency to treat populist attitudes as a single, monolithic construct. Dominated by the ideational approach, much of the existing literature neglects the role of the populist strongman and offers only limited conceptual clarity on authoritarian populism—particularly at the attitudinal level. To address this gap, we develop a more refined framework that moves beyond the standard definitional elements of the ideational model, demonstrating that populist attitudes consist of two distinct varieties. Using novel survey data from nine countries, we conduct a factor analysis that consistently reveals two components: one capturing anti-elitism and people-centrism (anti-establishment populism), and another reflecting majoritarianism, support for strongman rule, elitism, and exclusive nationalism (authoritarian populism). This underscores that the appeal of populist strongmen is rooted not in democratic ideals, but rather in the allure of authoritarian governance. Our findings show that in six countries—Italy, Hungary, Poland, Spain, Brazil, and Argentina—support for populist leaders is primarily driven by authoritarian populist attitudes. In contrast, anti-establishment populism emerges as the dominant factor only in France and Canada, while neither dimension has a significant effect in the United States.